Peripheral gangrene in polycythaemia vera. Issue 600 (October 1975) - Gétaz, Paul; Jacobs, Peter; Louw, Jannie H.
Abstract : A case of peripheral vascular disease which became gangrenous and led to a diagnosis of polycythaemia vera is described. Chemotherapy has been successful and surgical intervention avoided. The authors stress the importance of full haematological examination of any patient presenting with peripheral digital gangrene.